The Principle of Legal Balance and the Degradation of Incentive Rights in Protected Rice Field Policies - Mohammad Habib Ramdhani; Iwan Permadi; Indah Dwi Qurbani (Faculty of Law, Merdeka University Surabaya, Indonesia, 2026)
The increasing conversion of paddy fields to non-agricultural uses poses a significant threat to national food security, prompting the Indonesian Government to enact Presidential Regulation Number 4 of 2026 concerning the Control of Paddy Field Conversion. This regulation introduces a protection mechanism through the designation of Protected Paddy Fields (LSD) and imposes restrictions on landowners' rights to convert their agricultural land. As a balancing instrument, the regulation also provides incentives for individuals who maintain the agricultural function of their land. However, the incentive provisions contained in Articles 20 and 21 raise normative concerns, particularly due to the phrase